Interventions to reduce individual exposure of elderly individuals and children to haze: a review - Zhang, Sini (J Thorac Dis, 2016)
Given rapid economic developments and urbanization over the last few decades, China has experienced frequent haze episodes, which have adverse effects on public health. Children and elderly individuals are more susceptible than the general population to air pollution. In this study, we introduce interventions to reduce the exposure of elderly individuals and children to air pollution during hazy weather. These interventions include avoiding outdoor activities, wearing a dust mask, reducing burning biomass fuels, reducing frying and smoking at home, using an air filtration unit and taking supplemental antioxidants. However, the actual benefits of these measures remain unproven and are unlikely to be adequate. Sustained clean air policies remain the most important and efficient solution to reduce air pollution-related health effects.